PW 1628 Status of injury prevention research in nepal; a systematic review. (November 2018) - Mytton, Julie; Bhatta, Santosh; Thorne, Matthew; Pant, Puspa
Abstract : Background: In 2017 work commenced to establish a Nepal Injury Research Centre. To inform our activities it was necessary to review the evidence arising from existing injury research. Objectives To identify published literature reporting incidence or outcome of injuries sustained in Nepal and explore the quantity of research, types of injuries studied, quality and methodologies used, and the epidemiology reported. Methods: A systematic review of observational and experimental studies reporting injury rates or outcomes affecting populations resident in Nepal. Five electronic databases were searched, no language or date restrictions were applied. Case series of less than 10 persons were excluded. Data were extracted on design, methods and results and synthesised narratively. Findings: 175 studies were reported in 186 publications, identified from 3263 potentially eligible citations. Most were observational studies, often low in the hierarchy of evidence, with only 2/186 (1.1%) experimental studies. The types of injuries studied did not reflect the burden of injuries as perceived by stakeholders; only 21/186 (11.7%) publications focused on road traffic injuries despite this being a government priority. Most publications, 142/186 (76.3%), were case series, predominantly analyses of admissions to hospitals and likely to underestimate the true burden of injuries. Nationally representative community-based surveys were few but suggested an incidence of fatal injuries of ˜30/100000/yr, and of non-fatal injuries between 24.6–35.5/1000/yr. Conclusions: Acknowledging the risk of bias arising from observational data, these studies suggest that for every fatal injury there may be more than 100 non-fatal injuries in Nepal. Further research is needed to understand and prevent injuries causing the greatest burden, such as road traffic injuries. Developing capability in research methods should be a priority. Policy implications The existing evidence is likely to underestimate the true burden of injuries in Nepal and does not enable the development of evidence-based policies and legislation.